Infectious complications in the first year following autologous hematopoietic progenitor cell rescue for children with brain tumors. Issue 12 (17th August 2013) - Brown, Robert J.; Rahim, Hussein; Wong, Kenneth E.; Cooper, Robert M.; Marachelian, Araz; Butturini, Anna; Dhall, Girish; Finlay, Jonathan L.
Abstract Background High‐dose chemotherapy with autologous hematopoietic progenitor cell rescue (AuHPCR) for pediatric patients with brain tumors has become an important therapeutic modality to avoid or delay the long‐term effects of cranial irradiation. Data on post‐AuHPCR infectious complications in this population are lacking. This single institution retrospective review reports the prophylactic practices and infections in the first year following AuHPCR in pediatric patients with brain tumors. Procedure The medical record of patients who underwent AuHPCR for the treatment of a malignant brain tumor at Children's Hospital Los Angeles between 1988 and 2010 were reviewed. Patients without prior irradiation who were free of disease at 1 year without additional chemotherapy were evaluated for all infectious disease complications occurring from time of neutrophil engraftment to 1 year post‐AuHPCR. Results Forty‐three of the 115 eligible patients were included. The median time to neutrophil engraftment was 11 days (range: 8–43 days), and 20 Grade III/IV (no Grade V) infectious episodes developed in 15 patients (35%). Fourteen episodes of bacteremia (70%) were catheter‐related, predominantly gram‐negative (71%), and polymicrobial (50%). There were no fungal or pneumocystis infections and only 1 of 25 (4%) at‐risk patients developed VZV reactivation. Conclusions These data suggest patients with brain tumors undergoing AuHPCR have few late‐occurring non‐catheter‐related post‐transplant infections indicating that prophylaxis practices were sufficient. Central lines should be removed soon after engraftment, but those with central line infections should receive adequate treatment including gram‐negative coverage. In addition, only at‐risk patients who receive further irradiation may benefit from VZV reaction prophylaxis. Pediatr Blood Cancer 2013;60:2012–2017. © 2013 Wiley Periodicals, Inc.